Montaña de luz (Guillermo Centeno, 2005) et le programme cubain d’aide médicale internationale - Emmanuel Vincenot (Caravelle)
This paper tries to demonstrate that the documentary Montaña de luz (Guillermo Centeno, 2005), which praises the great achievements of the Cuban program of international medical aid, is representative of the ICAIC's tradition of propaganda cinema. The paper also tries to demonstrate that this movie, which insists on solidarity with developing countries, is paradoxically pervaded by a colonial imaginary.